INVESTIGATION OF THE EFFECT OF PLA2R1 POLYMORPHISM IN PATIENTS WITH MEMBRANOUS NEPHROPATHY - Aida Adıkozalova; Sebahat Usta Akgül; Erol Demir; Hayriye Şentürk Çiftçi; Fatma Savran Oğuz; Halil Yazıcı; Çiğdem Kekik Çınar (Sabiad)
Objective: Membranous nephropathy (MN) is the most common cause of nephrotic syndrome in adults. Phospholipase A2 receptor (PLA2R1) is a glycoprotein belonging to the mannose receptor family (~180 kDa). PLA2R1 was found to be associated with idiopathic MN pathogenesis, and the presence of PLA2R1 antibodies was supported by the diseases. In this study, the association of PLA2R1 rs35771982 with membranous nephropathy was investigated. Material and Methods: The study included 88 patients diagnosed with MN and 101 healthy individuals unrelated to the patients. The PLA2R1 rs35771982 levels of the patient and control groups were examined using the Real Time PCR (Polymerase Chain Reaction) method. Results: The comparison of the patients with healthy controls in this study showed that the rs35771982 GG genotype was significantly higher in the patients. The genotype of rs35771982 in the Turkish population was found to be common to the CG genotype. Conclusion: Our findings revealed that the PLA2R1 rs35771982 GG genotype is associated with susceptibility to MN.